Growth rate variability of larval European eels (Anguilla anguilla) across the extensive eel spawning area in the southern Sargasso Sea. (20th April 2018) - Ayala, Daniel Jiro; Munk, Peter
Abstract: The European eel ( Anguilla anguilla ) spawns in the Sargasso Sea, and the leptocephalus larvae are distributed in the Subtropical Convergence Zone (STCZ), covering an area approximately 500 × 2, 000 km in extent. The STCZ is hydrographically diverse and highly dynamic, which is likely to impact growth and survival opportunities of the larvae. Here we investigate the temporal and spatial growth rate variability of larvae collected along seven sampling transects across the STCZ during March–April 2014. Scanning electron microscopic analyses of otolith ring‐formations were used to estimate larval age‐at‐length, initial growth and growth trajectories. Analyzed larvae averaged 14 mm in length and 30 days of age. Age estimation indicated that the larvae were spawned during one continuous period, extending from mid‐February to late‐March, and that spawning had peaked during the new moon of 4 March. Growth estimates (average: 0.38 mm/day, ~6% weight increase/day) showed substantial variability among individuals. There were no apparent spatial trends in this variability, and no linkage to measures of temperature and salinity, while earlier‐spawned leptocephali showed slightly higher growth rates than later‐spawned larvae. The variability in growth rates at single sampling sites was as great as variability across the entire area of distribution. This indicates that individual growth opportunities are strongly impacted by variable conditions in the immediate environment while average conditions for larval growth and survival are basically the same throughout the immense area of larval distribution.